A useful preparation of ultrasmall iron oxide particles by using arc plasma deposition. Issue 68 (14th November 2020) - Ida, Yumi; Okazawa, Atsushi; Sonobe, Kazutaka; Muramatsu, Hisanori; Kambe, Tetsuya; Imaoka, Takane; Chun, Wang-Jae; Tanabe, Makoto; Yamamoto, Kimihisa
Abstract : Finely size-controlled ultrasmall iron oxide particles (IOPs) on graphene nanosheets were usefully prepared by using pulsed arc plasma deposition. The IOPs are composed of a high crystallinity single γ-Fe2 O3 component without annealing. Abstract : Ultrasmall particles, different from the larger size nanoparticles, have recently attracted significant attention in the scientific community in nanotechnology for catalytic, electronic and optical applications; however, their magnetic properties remain unexplored due to the difficult structural analysis. A challenging issue is to develop a preparation method for iron oxide particles (IOPs) with fine size control, and to determine the dependence of magnetic properties on the morphology and crystallinity of the magnetic particles. However, synthetic approaches to obtain IOPs, regarded as one of the new fields of magnetic nanoparticles, have been significantly limited. This article reported a developed synthetic method to prepare IOPs on carbon supports using pulsed arc plasma deposition (APD) in flowing oxygen gas, which clarified the finely-controlled formation of IOPs on graphene nanosheets. Structural characterization of the IOPs revealed the formation of crystalline γ-Fe2 O3 ultrasmall particles with oxygen deficiency. The pulsed APD method for IOPs is the first simple and convenient technique to not only prevent significant aggregation and contamination by organic compounds and avoid the need for thermal pretreatment, but also provide uniform crystalline nano-order particles.